Implementasi dan Pelatihan Enterprise Resource Planning Odoo untuk Peningkatan Efisiensi Proses Bisnis di Enzzo - Stephanie, Stephanie; Davidsen Cuaca; Owen Felix; Rosita Darianty; Ade Maulana (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
The rapid development of technology has encouraged companies to adopt ERP systems in their business processes to enhance efficiency and competitiveness in the market. However, not many SMEs implements information technology into their business, including Enzzo Locks, an SME operating as a distributor of lock products. It is apparent that Enzzo Locks faces difficulties in managing their financial reports and inventory, which are still managed manually. The proposed solution is the implementation of the Odoo system. The method includes analysing the partner's needs, selecting Odoo modules according to their needs, and conducting training to enhance operational understanding of the system. The implementation results show that the Odoo system can assist in managing business processes, although there are some challenges remain, such as the system’s UI that is less user-friendly and the discrepancies between the accounting module and the partner's expectations. To ensure sustainability, adjustments to the Odoo system and regular training are necessary to ensure the partner can operate the system more effectively. Based on the results achieved, this initiative has significantly contributed to improving the efficiency and effectiveness of business management through information technology and supports the sustainability of SMEs in the digital era.  However, continuous customization and training are required in order to get the most out of Odoo.